(untitled) (World Economics and Finance Bulletin, 2026)
This article analyzes the issues of protecting human rights and freedoms in the digital world. The rapid development of modern information and communication technologies creates significant opportunities, but also generates new risks and challenges. In particular, issues such as cybercrime, violations of personal data privacy, digital surveillance, and ethical concerns related to artificial intelligence are examined. The article explores these problems based on the experience of Uzbekistan and international practices, and proposes possible solutions